Ruminal degradation of dry matter and neutral detergent fiber of banana peel treated with limestone - Monção, Flávio Pinto [UNESP]; Dos Reis, Sidnei Tavares; Rigueira, João Paulo Sampaio; De Sales, Eleuza Clarete Junqueira; Alves, Dorismar David; De Aguiar, Ana Cássia Rodrigues; De Oliveira, Euclides Reuter; Júnior, Vicente Ribeiro Rocha (Universidade Estadual de Londrina, 2016)
This study aimed to evaluate the kinetics of dry matter degradation and neutral detergent fiber of banana peel treated with limestone. The banana peel has been acquired from a candy manufacturer that after washing with chlorinated water to 1% and pulp removal was discarded. The banana peel in nature was treated with 1, 2, 3 and 4% of limestone in the natural matter, homogenized and pre-dried in the sun for 120 hours. The experiment was conducted in a completely randomized experimental design, with five treatments (0 (control), 1, 2, 3 and 4% inclusion of limestone) with 3 repetitions. The dry matter potential degradability, showed no difference (P>0.05) in the levels compared to the control with an average of 67.58%. The insoluble degradation fraction rate of dry matter and the fiber fraction did not differ (P> 0.05) between levels and control. In relation to effective degradability of neutral detergent fiber, there was an increase of 3.47% for each percentage unit increased limestone. In relation to the ruminal degradation parameters of dry matter and neutral detergent fiber is not recommended the utilization of limestone as an additive in the treatment of banana peel.
Keywords: Calcium oxide; Coproducts; Degradability; Feed evaluation; Ruminants